Non-invasive measures of core temperature versus ingestible thermistor during exercise in the heat - Fogt, D. L.; Henning, A. L.; Venable, A.; McFarlin, B. K. (International Journal of Exercise Science, 2016)
The accuracy of core temperature (Tc) thermometry from temporal, tympanic, and oral thermometry devices has been variable during exercise in a hot, humid environment. The purpose of the present study was to cross-validate temporal, two tympanic devices, and oral devices compared to an ingestible thermistor during exercise in a hot, humid environment. Fourteen young, active adults (6 women) completed a graded exercise test until voluntary exhaustion in an environmental chamber (35.5 ± 0.6 °C, 53.9 ± 5.8 % RH). There was no statistical difference in mean temperature between tympanic device 1 and pill-based core temperature (PBTc) measurements across all time points and were positively correlated (0.357; P<0.001). Temperatures of tympanic device 2 were statistically higher than PBTc (37.8 ± 0.7 ºC vs. 37.6 ± 1.0 ºC; respectfully) (P=0.008). At all time points, temperatures for the second tympanic device and PBTc were positively correlated (0.192; P=0.043). Temporal and PBTc values did not differ across time points and were positively correlated (0.262; P=0.005) across all time points. Mean oral temperature was significantly less than mean PBTc across all time points. (37.0 ± 0.4 ºC vs. 37.6 ± 1.0 ºC, respectively) (P<0.001). Across all time points, oral and PBTc were positively correlated (0.262; P=0.010). Tympanic and temporal devices can reflect Tc while exercising in a hot, humid environment. However, care should be taken when selecting the tympanic or temporal measurement device and validation is advised prior to heat illness mitigation in the field.